General anesthesia or conscious sedation in paroxysmal atrial fibrillation catheter ablation - Moravec, Ondrej; Skala, Tomas; Klementova, Olga; Skalova, Jitka; Hutyra, Martin; Precek, Jan; Fedorco, Marian; Cernicek, Vlastimil; Tudos, Zbynek; Zapletalova, Jana; Taborsky, Milos (Biomedical papers, 2021)
Background. Catheter ablation of paroxysmal atrial fibrillation (AF) can be performed under general anesthesia or conscious sedation. The influence of type of anesthesiology care on procedural characteristics and ablation outcome in patients in whom intracardiac echocardiography (ICE) and elimination of adenosine-mediated dormant conduction (DC) is used is not entirely known. Methods. 150 patients with paroxysmal AF were randomized to point-by-point radiofrequency catheter isolation of pulmonary veins (PVI) under general anesthesia (n=77) or conscious sedation (n=73). Adenosine-mediated dormant conduction was eliminated in all patients. Antiarrhythmic medication was discontinued after PVI. During twelve months of follow-up, all patients underwent four times 7-day ECG monitorings. Results. There was no difference between groups in AF recurrence (28.6% vs. 31.5%, P=0.695). Patients in conscious sedation had longer procedure times (160 extpm 32.1 vs. 132 extpm 31.5 min, P<0.001), longer RF energy application times (40 extpm 15 vs. 29 extpm 11 min, P<0.001) and longer fluoroscopy times (6.2 min extpm 5.3 vs. 4.3 min extpm 2.2, P<0.001) with similar complication rates. Conclusion. Conscious sedation is not inferior to general anesthesia in regard to arrhythmia recurrence or complication rates of catheter ablation of paroxysmal atrial fibrillation. However, it is associated with longer procedure times, longer time of radiofrequency energy application and longer fluoroscopy times.
Keywords: general anesthesia; conscious sedation; atrial fibrillation; catheter ablation; adenosine; dormant conduction; arrhythmia recurrence; intracardiac echocardiography